The NSP elite study program as a foreign policy instrument of Taiwan’s new southbound policy toward Indonesia - Siti Mufidah Ainun Nabila; Moh. Fathoni Hakim (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2026)
In the context of Taiwan's New Southbound Policy toward Indonesia, this study examines the role of the New Southbound Policy Elite Study Program (NSPESP) as a foreign policy instrument. As Taiwan faces structural diplomatic constraints, non-traditional approaches have become increasingly important in promoting international engagement. However, previous studies have largely focused on the policy framework and its economic dimensions, leaving limited understanding of how specific programs function as foreign policy instruments at the implementation level. Drawing on Christopher Hill’s framework, which emphasizes the transformation of resources into capabilities and instruments, this study analyzes how NSPESP operates as a foreign policy instrument. This research employs a qualitative descriptive approach and document analysis, utilizing official policy documents, program materials, and institutional communications. The findings reveal that Taiwan mobilizes its strategic resources—including technological expertise, sustainability initiatives, and cultural assets—through institutional coordination among government agencies, academic institutions, and overseas representative offices. These resources are systematically translated into programmatic themes and implemented through structured processes such as participant recruitment, academic engagement, and scheduled program activities. Beyond facilitating knowledge exchange, these activities also serve as mechanisms of cultural engagement. The study concludes that NSPESP functions as a non-coercive foreign policy instrument that enables Taiwan to navigate its diplomatic constraints while strengthening relations with partner countries, including Indonesia. Within the broader framework of Taiwan’s foreign policy, the program demonstrates how structured engagement can effectively connect domestic capabilities with external foreign policy objectives.